Impact of individual platelet lysates on isolation and growth of human mesenchymal stromal cells - Horn, Patrick; Bokermann, Gudrun; Cholewa, Dominik; Bork, Simone; Walenda, Thomas; Koch, Carmen; Drescher, Wolf; Hutschenreuther, Gabriele; Zenke, Martin; Ho, Anthony Dick; Wagner, Wolfgang (Cytotherapy, 2010)
Background aims - Culture medium for mesenchymal stromal cells (MSC) is frequently supplemented with fetal calf serum (FCS). FCS can induce xenogeneic immune reactions, transmit bovine pathogens and has a high lot-to-lot variability that hampers reproducibility of results. Several studies have demonstrated that pooled human platelet lysate (HPL) provides an attractive alternative for FCS. However, little is known about the variation between different platelet lysates. - Methods - We compared activities of individual HPL on initial fibroblastoid colony-forming units (CFU-F), proliferation, in vitro differentiation and long-term culture. These data were correlated with chemokine profiles of HPL. - Results - Isolation of MSC with either HPL or FCS resulted in similar CFU-F frequency, colony morphology, immunophenotype and adipogenic differentiation potential. Osteogenic differentiation was even more pronounced in HPL than FCS. There were significant differences in MSC proliferation with different HPL, but it was always higher in comparison with FCS. Cell growth correlated with the concentration of platelet-derived growth factor (PDGF) and there was a moderate association with platelet counts. All HPL facilitated expansion for more than 20 population doublings. - Conclusions - Taken together, reliable long-term expansion was possible with all HPL, although there was some variation in platelet lysates of individual units. Therefore the use of donor recipient-matched or autologous HPL is feasible for therapeutic MSC products.